2012
DOI: 10.1128/jvi.05657-11
|View full text |Cite
|
Sign up to set email alerts
|

Viral Interferon Regulatory Factors Are Critical for Delay of the Host Immune Response against Rhesus Macaque Rhadinovirus Infection

Abstract: Kaposi's sarcoma (KS)-associated herpesvirus (KSHV) is a gamma-2 gammaherpesvirus that was identified in 1994 to be the cause of AIDS-related KS (11), one of the most common malignancies within human immunodeficiency virus (HIV)-infected individuals. KSHV establishes a persistent infection within B cells (2,14) and is also associated with the malignant B cell disorders, multicentric Castleman's disease (MCD), and primary effusion lymphoma (PEL) (9, 48). Patients who develop MCD and PEL often have a poor outcom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
18
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 53 publications
0
18
0
Order By: Relevance
“…KSHV and rhesus macaque rhadinovirus (RRV), the two highly related gammaherpesviruses, are the only viruses known to (146). Collectively, these findings demonstrate that both KSHV and RRV vIRFs have a broad impact on herpesvirus pathogenesis and host immune responses.…”
Section: Discussionmentioning
confidence: 88%
“…KSHV and rhesus macaque rhadinovirus (RRV), the two highly related gammaherpesviruses, are the only viruses known to (146). Collectively, these findings demonstrate that both KSHV and RRV vIRFs have a broad impact on herpesvirus pathogenesis and host immune responses.…”
Section: Discussionmentioning
confidence: 88%
“…Virus particles with gold particles are indicated by the white arrowhead, and virus particles with no gold particles are indicated by black arrowheads. nificant differences in the antiviral state early during infection (33,34). The RRV vIRFs were found to be responsible for a decrease in gene expression and IFN production, as well as decreased nuclear accumulation of pIRF3 during de novo infection with RRV.…”
Section: Discussionmentioning
confidence: 98%
“…In addition, type I IFNs have dramatic effects on natural killer (NK) cells (49,50) and CD4 ϩ and CD8 ϩ T cells (51,52), as well as dendritic cells (DCs) (53)(54)(55)(56). In fact, it was previously shown that complete deletion of all 8 RRV vIRFs initiates an earlier T cell response (34), and therefore, it could be postulated that the IFN-␤ inhibition mediated by virion-associated R6 contributes to the delayed T cell response observed in WT RRV infection. It would be particularly interesting to create an R6 deletion mutant of RRV and to determine the phenotype of this virus and the ensuing immune response.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations